Responsibility and control : a theory of moral responsibility / John Martin Fischer, Mark Ravizza. - Fischer, John Martin, 1952-; Ravizza, Mark, 1958- (Cambridge studies in philosophy and law., 1998)
This book provides a comprehensive, systematic theory of moral responsibility. The authors explore the conditions under which individuals are morally responsible for actions, omissions, consequences, and emotions. The leading idea in the book is that moral responsibility is based on 'guidance control'. This control has two components: the mechanism that issues in the relevant behavior must be the agent's own mechanism, and it must be appropriately responsive to reasons. The book develops an account of both components. The authors go on to offer a sustained defense of the thesis that moral responsibility is compatible with causal determinism.